60‐3: Invited Paper: Active‐Matrix Digital Microfluidics System for Single Cells Manipulation. Issue 1 (28th June 2022) - Wang, Dongping; Hu, Siyi; Ma, Hanbin
Abstract : The emerging microfluidic tools bring new methods for miniaturized analytical systems and single cells manipulation. This study presents an active‐matrix digital microfluidic platform for single cells generation and manipulation. The microfluidic chip was fabricated by amorphous silicon (a‐6i) thin‐film transistor (TFT) technology. The active device contains 26, 368 electrodes that can be independently addressed to perform multiple and simultaneous droplets manipulation. The electrode array consists of electrodes differing in shape and size. The combination of various electrodes can give full play of their advantages, thus improve the droplet movement stability and generation uniformity. This work paves new ways for conducting low‐cost and high‐throughput applications in single cells manipulation.